Answer:
−a^2 b^2 + 2a + 2b
_________________
a^2
Step-by-step explanation:
<u><em>Please mark as brainliest if answer is right</em></u>
Have a great day, be safe and healthy
Thank u
XD
You can’t solve this, not enough information
Answer:
-cos^4(x)
Step-by-step explanation:
Step 1: Use the Pythagorean identity : 1=cos^2(x) + sin^2(x)
1-sin^2(x) = cos^2(x)
-1+sin^2(x) = -cos^2(x)
cos^2(x) (-cos^2(x))
Step 2: Factor out common terms cos^2(x)
cos^2(x) (sin^2(x)-1)
Ans: -cos^4(x)
Answer:
9% = 450
10% = 500
8% = 400
Step-by-step explanation: